2011
DOI: 10.1038/ki.2010.555
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of urinary biomarkers of acute kidney injury in the critically ill by stratification for injury duration and baseline renal function

Abstract: To better understand the diagnostic and predictive performance of urinary biomarkers of kidney injury, we evaluated γ-glutamyltranspeptidase (GGT), alkaline phosphatase (AP), neutrophil-gelatinase-associated lipocalin (NGAL), cystatin C (CysC), kidney injury molecule-1 (KIM-1), and interleukin-18 (IL-18) in a prospective observational study of 529 patients in 2 general intensive care units (ICUs). Comparisons were made using the area under the receiver operator characteristic curve (AUC) for diagnosis or predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
251
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(270 citation statements)
references
References 38 publications
11
251
2
6
Order By: Relevance
“…In a more recent report of urine biomarkers obtained during the EARLARF trial, in which no differences were seen (i.e., development of AKI in 48 hours, need for dialysis, or death in 7 days) between erythropoietin and placebo on admission to the ICU (31), five of the six biomarkers studied predicted death within 7 days with AUCs from 0.61 to 0.68 (32). Urine NGAL, IL-18, and cystatin C also predicted the need for dialysis with AUCs from 0.71 to 0.79.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent report of urine biomarkers obtained during the EARLARF trial, in which no differences were seen (i.e., development of AKI in 48 hours, need for dialysis, or death in 7 days) between erythropoietin and placebo on admission to the ICU (31), five of the six biomarkers studied predicted death within 7 days with AUCs from 0.61 to 0.68 (32). Urine NGAL, IL-18, and cystatin C also predicted the need for dialysis with AUCs from 0.71 to 0.79.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown previously in many clinical studies and has been accepted that NGAL and Cystatin C levels increase in different clinical settings leading to AKI development [10][11][12][13][14][15][16][17][18][19][20][21][22]. Since the aim of this study is to define the roles of Cystatin C and NGAL in predicting septic AKI development, the patients who had other risk factors, rather than sepsis, that would lead to AKI and increase the Cystatin C and NGAL levels (i.e., nonseptic-AKI patients) were excluded from the study.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…They are investigated in different clinical settings including cardiac surgery [10], contrast agent use [11], critically ill patients [12][13][14][15][16][17][18][19][20][21] and in emergency department [22].…”
Section: Introductionmentioning
confidence: 99%
“…203 participants died of which 90 died of cardiovascular causes. Total mortality incidence rate (95% CI) was 50 (44-58) and cardiovascular mortality incidence rate 22 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) per 1000 person-years.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The remaining CysC is eliminated in the urine and urinary CysC (u-CysC) concentrations are thus normally very low [9][10][11]. Tubular dysfunction reduce the degradation leading to a subsequent increase in uCysC concentrations and several studies have suggested that u-CysC is a reliable biomarker of acute tubular damage [5,[12][13][14][15][16][17][18][19][20] and worse prognosis [16,19] in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%